Utilidad del Deep Learning en la predicción del fracaso empresarial en el ámbito europeo; The usefulness of Deep Learning in the prediction of business failure at the European level - Mariano Romero Martínez; Pedro Carmona Ibá\~nez; José Pozuelo Campillo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– In this paper we intend to substantiate the usefulness of Deep Learning, especially feedforward neuronal networks, in the prediction of business failure. This methodology provides very good results in terms of predictive performance when large sample sizes are available. Therefore, we have developed a business failure prediction model for European companies, based on this algorithm on a sample of 61,624 companies, of which 12,128 were declared bankrupt in 2016. As independent variables were considered ratios, and economic and financial data obtained from the financial statements for the year preceding the date of failure. Deep Learning achieves a predictive performance of 94%, where companies with larger size and lower solvency are more prone to failure. The obtained results have been tested on an independent test sample, different from that used to estimate and train the model.
Keywords: C53; 330; business failure; Deep Learning; machine learning; financial ratios; prediction model